2018
DOI: 10.1097/hpc.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

A New Feasible Syncope Risk Score Appropriate for Emergency Department: A Prospective Cohort Study

Abstract: The 3 syncope risk scores could somehow predict 3-month adverse events. We found more feasible indicators that could predict serious events better. It suits well for emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study calculated a sensitivity of 96.8% and a specificity of 72.8%, which may allow more accurate stratification and targeting of diagnostic procedures and therapeutic interventions. Similarly, other studies [ 15 , 18 , 20 , 32 - 34 ] have validated the OESIL risk score using different study designs, different endpoints, and different individuals who interpreted the ECG. The results suggested that the prediction accuracy of OESIL in other syncope populations is significantly reduced, so it has not been promoted in clinical applications.…”
Section: Prognostic Scores For Long-term Outcomesmentioning
confidence: 96%
“…The study calculated a sensitivity of 96.8% and a specificity of 72.8%, which may allow more accurate stratification and targeting of diagnostic procedures and therapeutic interventions. Similarly, other studies [ 15 , 18 , 20 , 32 - 34 ] have validated the OESIL risk score using different study designs, different endpoints, and different individuals who interpreted the ECG. The results suggested that the prediction accuracy of OESIL in other syncope populations is significantly reduced, so it has not been promoted in clinical applications.…”
Section: Prognostic Scores For Long-term Outcomesmentioning
confidence: 96%
“…Less is known of the importance of syncope in the prognosis of the patients with traumatic head injury. The long-term prognosis in head trauma patients may be related not only to the severity of head injury but also to the underlying condition, which predisposes to trauma such as alcoholism, drug addiction, or concomitant chronic diseases (16)(17)(18)(19)(20). The aim of this study was to assess whether syncope as a cause of head trauma affects short-and long-term prognosis in patients presenting with head injury.…”
Section: Introductionmentioning
confidence: 99%